Pengembangan Media Pembelajaran Interaktif "Toko Kue Pecahan" Berbasis HTML5 dan GSAP melalui pendekatan RME untuk Siswa Kelas V SD Negeri Kragilan 03 - Khasanah, Uswatun; Sudiyana, Benedictus; Sadino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The utilization of digital technology in mathematics learning at the elementary school level has not been optimal, despite the availability of Interactive Flat Panel (IFP) facilities. This condition causes fraction learning to remain dominated by conventional methods, making abstract concepts difficult for students to understand. This study aimed to develop an interactive learning media entitled "Fraction Cake Shop" based on HTML5 and the GreenSock Animation Platform (GSAP) through the Realistic Mathematics Education (RME) approach for fifth-grade students at SD Negeri Kragilan 03. The research apply the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 18 fifth-grade students. Data were collected through validation sheets from media experts, material experts, instructional experts, and student response questionnaires, then analyzed descriptively using quantitative percentage techniques. The results showed that the media achieved a very valid category, with validation percentages of 92.83% from media experts, 87.4% from material experts, and 90% from instructional experts. Student responses reached 93.5% in the very good category, while the media usability aspect obtained 94.1% and the student response aspect obtained 91.0%. The media was able to present fraction concepts in a more concrete form, thereby facilitating students’ understanding of the material. In addition, it increased learning motivation, optimized the use of the Interactive Flat Panel (IFP) in the learning process, and developed students’ critical thinking skills and independence. Therefore, the "Fraction Cake Shop" learning media is considered feasible for use as a mathematics learning medium in elementary schools.